A COMPARATIVE ANALYSIS OF THE PROPOSED MANDATORY NATURE OF EMPLOYMENT LEGISLATION AND ITS INTERACTION WITH THE CHOICE OF LAW OF AN INTERNATIONAL CONTRACT (The Pretoria Student Law Review, 2021)
In an ever-changing world characterised by globalisation there has been a steep increase in employment contracts with an international character. This may lead to a conflict of laws whereby a forum court is confronted with the application of either the forum’s domestic laws or those of a foreign judicial system. In these cases we are confronted with the interaction between party autonomy and the limitations placed on the exercise thereof. The international legal community has yet to reach a consensus on the requirements of the exercise of party autonomy, and thus there are no ‘supra-national laws’ governing party autonomy.1 Only in extraordinary circumstances will the forum court divert from the proper law of the contract and in doing so veer from the principle of freedom to contract.2 This is illustrated in Louks v Standard Oil Company of New Jersey3 where Cardoza CJ stated so congruously in his obiter that ‘we are not so provincial as to say that every solution of a problem is wrong because we deal with it otherwise at home4.’ This article will endeavour to give an overview of the interaction between the proper law of a contract as chosen by the contracting parties in an international contract and the mandatory rules of a forum court that may be under consideration. This article will undertake a critical comparison and analysis of the methods and reasoning applied by the courts in the jurisdictions of New Zealand, the United Kingdom and South Africa in respect of the mandatory nature of employment legislation and its interaction with the choice of law of an international employment contract. This will be done in reference to a specific company, Cathay Pacific, its employment contracts and the court cases that flowed from the choice of law clause in the contracts between Cathay Pacific and its employees in both New Zealand and the United Kingdom. A discussion of the possible repercussions of such a clause in a South African legal context will follow.
Keywords: international employment contracts; domestic laws; foreign judicial system; conflict of laws; New Zealand; South Africa